2020
DOI: 10.1093/biolinnean/blaa020
|View full text |Cite
|
Sign up to set email alerts
|

Cranial integration in the fire salamander, Salamandra salamandra (Caudata: Salamandridae)

Abstract: Phenotypic integration and modularity are concepts that represent the pattern of connectivity of morphological structures within an organism. Integration describes the coordinated variation of traits, and analyses of these relationships among traits often reveals the presence of modules, sets of traits that are highly integrated but relatively independent of other traits. Phenotypic integration and modularity have been studied at both the evolutionary and static level across a variety of clades, although most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 63 publications
6
25
1
Order By: Relevance
“…Previous work has shown that the strength of integration can facilitate (Navalon et al 2020;Fabre et al 2020;Randau & Goswami 2017a), constrain (Goswami & Polly 2010b;), or have no recoverable effect on morphological diversity (paedomorphic salamanders in Fabre et al 2020;Bardua et al 2019b;Watanabe et al 2019;Bon et al 2020). Here, we find that neither the strength of within-bone integration nor the average strength of each bone's association with another has a significant effect on morphological diversity (Fig.…”
Section: Does the Magnitude Of Morphological Integration Constrain Mocontrasting
confidence: 60%
See 1 more Smart Citation
“…Previous work has shown that the strength of integration can facilitate (Navalon et al 2020;Fabre et al 2020;Randau & Goswami 2017a), constrain (Goswami & Polly 2010b;), or have no recoverable effect on morphological diversity (paedomorphic salamanders in Fabre et al 2020;Bardua et al 2019b;Watanabe et al 2019;Bon et al 2020). Here, we find that neither the strength of within-bone integration nor the average strength of each bone's association with another has a significant effect on morphological diversity (Fig.…”
Section: Does the Magnitude Of Morphological Integration Constrain Mocontrasting
confidence: 60%
“…In any case, our developmental modularity hypotheses, which considered the embryonic origins of the articular and quadrate (splanchnocranium) and the rest of the feeding bones (dermatocranium), were not well supported (Supplementary Table 5). While additional patterns of developmental integration potentially contributing to morphological integration in the snake skull are less understood but surely exist, the high amount morphological integration in the kinetic feeding system of snakes is striking when considering the complex patterns of modularity recovered from the synostotic bones that make up akinetic morphological structures in mammals (Goswami 2006;Martín-Serra et al 2018;Adams & Collyer 2019), archosaurs Felice et al 2019), and amphibians (Marshall et al 2019;Bon et al 2020;Fabre et al 2020). In the feeding system of aquatic-foraging snakes, we recognize strong functional and evolutionary integration generated because of its kinesis and developmental disintegration.…”
Section: The Hyperkinetic Feeding System Is Highly Integratedmentioning
confidence: 99%
“…2020; Bon et al. 2020). Here, we find that neither the strength of within‐bone integration nor the average strength of each bone's association with another has a significant effect on morphological diversity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2019b) and salamander (Bon et al. 2020; Fabre et al. 2020) crania, despite substantial morphological differences among these clades.…”
Section: Discussionmentioning
confidence: 99%